Understanding precipitate evolution during friction stir welding of Al-Zn-Mg-Cu alloy through in-situ measurement coupled with simulation. (15th April 2018) - dos Santos, J.F.; Staron, P.; Fischer, T.; Robson, J.D.; Kostka, A.; Colegrove, P.; Wang, H.; Hilgert, J.; Bergmann, L.; Hütsch, L.L.; Huber, N.; Schreyer, A.
Abstract: Friction Stir Welding (FSW) imparts both heat and deformation to the metal being joined, producing profound microstructural changes that determine the weld properties. In the case of welding of aerospace aluminium alloys, the most important change is the modification of the size, nature, and fraction of strengthening precipitates. To understand these changes requires the ability to measure the microstructural evolution during the welding process. This paper describes a new tool, the FlexiStir system, a portable friction stir unit designed for use in a high-energy synchrotron beamline that enables in-situ studies of microstructural evolution during FSW. FlexiStir has been used to measure precipitate evolution during FSW of aluminium alloy 7449-TAF and provide time-resolved measurement of precipitate size and volume fraction via small angle X-ray scattering (SAXS). These measurements have been interpreted with the aid of a previously developed microstructural model. The model predictions and SAXS measurements are in good qualitative agreement and demonstrate the complex precipitate transformation, dissolution, and reprecipitation events that occur during welding. Graphical abstract: Image 1